2015
DOI: 10.1093/jxb/erv091
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of RNA polymerase II in Arabidopsis interphase nuclei

Abstract: HighlightSuper-resolution microscopy reveals the number of RNA polymerase II molecules in plant interphase nuclei. Both active and inactive polymerase variants aggregate in a range known from mammalian transcription factories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 90 publications
2
48
0
Order By: Relevance
“…We used antibodies specific for the elongating form (phosphorylated at Ser2 of the CTD repeats) and specific for the nonphosphorylated form of RNAPII. In Arabidopsis interphase nuclei, the majority of RNAPII is globally dispersed in the euchromatic part of the nucleoplasm (Schubert and Weisshart, 2015). Consistently, our SIM analyses revealed that ELF7/SPT6L and both forms of RNAPII comprised separate, dispersed, reticulate structures within the euchromatin, but they were absent from the nucleolus and heterochromatin ( Figure 3).…”
Section: Elf7 and Spt6l Colocalize With Rnapii In Euchromatinsupporting
confidence: 76%
“…We used antibodies specific for the elongating form (phosphorylated at Ser2 of the CTD repeats) and specific for the nonphosphorylated form of RNAPII. In Arabidopsis interphase nuclei, the majority of RNAPII is globally dispersed in the euchromatic part of the nucleoplasm (Schubert and Weisshart, 2015). Consistently, our SIM analyses revealed that ELF7/SPT6L and both forms of RNAPII comprised separate, dispersed, reticulate structures within the euchromatin, but they were absent from the nucleolus and heterochromatin ( Figure 3).…”
Section: Elf7 and Spt6l Colocalize With Rnapii In Euchromatinsupporting
confidence: 76%
“…Highly transcribed genes showed a tendency to couple in our data, suggesting that there is "AB" On the other hand, when we examined chromatin loops smaller than 6 kb, we found that a subset of them had strong Pol II binding on both interacting partners (Fig. 4D, highlighted with an arrow), perhaps reflecting active RNA polymerases aggregated within short distances (Schubert and Weisshart 2015). To address whether this pattern arises from interactions between highly expressed genes located close to each other in the genome and/or interactions within the same gene body, we focused on Pol II ChIPseq peaks in small chromatin loops.…”
Section: Transcribed Genes Do Not Show Strong Preference To Couplementioning
confidence: 66%
“…This model has been refined using advanced microscopy techniques. While the majority of active RNA Pol II molecules are globally dispersed in both animal and plant nuclei, a small subset forms clusters (Schubert 2014;Zhao et al 2014;Schubert and Weisshart 2015). To ask whether highly expressed genes that are at least 6 kb apart are more likely to interact with each other than less highly expressed genes, we selected genes based on their transcript levels, which correlated with Pol II binding (Fig.…”
Section: Transcribed Genes Do Not Show Strong Preference To Couplementioning
confidence: 99%
“…Such studies include the mapping of RNA polymerase II in interphase nuclei of Arabidopsis in fixed samples with Cy and AlexaFluor fluorophores (Schubert and Weisshart, 2015) and the visualization of cortical microtubules in fixed root cells immunolabeled with antibodies conjugated to the photoswitchable fluorophore AlexaFluor 647 at a resolution of approximately 50 nm (Dong et al, 2015).…”
Section: Single-molecule Localization Microscopymentioning
confidence: 99%